Adalimumab or infliximab as monotherapy, or in combination with an immunomodulator, in the treatment of Crohn's disease. Issue 10 (26th September 2016) - Cosnes, J.; Sokol, H.; Bourrier, A.; Nion‐Larmurier, I.; Wisniewski, A.; Landman, C.; Marteau, P.; Beaugerie, L.; Perez, K.; Seksik, P.
Summary: Background: The comparative efficacy of adalimumab (ADA) and infliximab (IFX) in Crohn's disease, and the benefit of initial combotherapy with an immunomodulator, are debated. Aim: To assess the best anti‐TNF treatment regimens in Crohn's disease. Methods: We included 906 biologic‐naïve Crohn's disease patients [median age, 31 years (24–41)] and performed a retrospective analysis of 1284 therapeutic exposures to ADA ( n = 521) or IFX ( n = 763) between 2006 and 2015. An immunomodulator was associated during the first 4–6 months (initial combotherapy) during 706 therapeutic exposures (55%). Median duration of anti‐TNF therapy was 39 months (IQR 17–67). Primary outcomes were 6‐month and 2‐year response rates and drug survival. Logistic regression with propensity scoring and Cox proportional hazard analysis determined variables associated with outcomes. Results: The response rates at 6 months and 2 years were 64% and 44% on ADA mono, 86% and 70% on ADA combo, 72% and 45% on IFX mono, and 84% and 68% on IFX combotherapy, respectively. Differences between ADA and IFX were not significant, whereas combotherapy was superior to monotherapy ( P < 0.001). Drug survival was longer with combotherapy vs. monotherapy [adjusted hazard ratio 2.17 (1.72–2.70)] and not significantly different between ADA and IFX. During subsequent anti‐TNF exposures, IFX combotherapy fared better than other groups regarding response rates, drug survival, disease activity, hospitalisations and abdominal surgery. Conclusion: In this retrospective analysis of a large tertiary centre cohort of Crohn's disease patients, ADA and IFX had similar efficacy as first line treatment, while initial combotherapy with an immunomodulator improved all outcome measures.